Inverse Linking: Taking Scope with Dependent Types - Grudzinska, Justyna; Zawadowski, Marek (Proceedings of the Amsterdam Colloquium, 2025)
Inverse linking constructions (ILCs) refer to complex DPs which contain a quantified NP (QP) which is selected by a preposition (e.g. a representative of every country). ILCs have been known to be ambiguous between a surface-scope reading and an inverse-scope reading. One puzzling difficulty for the existing accounts of ILCs is that some prepositions (e.g. with) block inverse-scope interpretations. In this paper, we propose a new dependent type analysis of the two readings of ILCs. In our analysis, we follow Zimmermann (2002) and assume that ILCs are structurally ambiguous at surface structure: the two readings of ILCs derive from the two (string identical) surface structures. The advantage of our dependent type account over Zimmermann’s analysis is that it interprets the surface structure for the inverse-scope reading in a fully compositional way. Other compositional non-movement accounts of ILCs have been proposed; however, our dependent type account is the first to offer a principled solution to the puzzle of why inverse-scope readings are blocked with certain prepositions.